Effect of Regret Aversion and Information Cascade on Investment Decisions in the Real Estate Sector: The Mediating Role of Risk Perception and the Moderating Effect of Financial Literacy - Wangzhou, Kaixin; Khan, Mahnoor; Hussain, Sajjad; Ishfaq, Muhammad; Farooqi, Rabia (Frontiers in Psychology, 2021)
The real estate sector plays a significant role in the economy of any country. However, many investors irrational investments in the real estate market. Therefore, the purpose of this study is to assess the effects of regret aversion and information cascade on investment decisions while considering the moderating role of financial literacy and the mediating effect of risk perception in the real estate sector of developing countries. This research utilized a quantitative research technique, collecting data by distributing structured questionnaires to real estate investors, followed by convenience sampling. This study used both descriptive and inferential statistics to make the data more meaningful. SPSS 25.0 was utilized to interpret the data. Cronbach’s Alpha was used to test for internal consistency, while validity was checked through correlation. Confirmatory factor analysis (CFA) was applied to confirm that the items on the questionnaire are perfectly loaded on its construct. Furthermore, process macro, model 5, was used to investigate the moderation mediation. This work addresses a gap in the literature by studying financial literacy as a moderator and risk perception as a mediating variable in regret aversion bias and information cascade bias’s relationships with investment decisions in the real estate sector. The results confirmed that financial literacy weakens the negative effect of behavioral biases (regret aversion and information cascade) on investment decisions. In addition, risk perception mediates the relationships between these cognitive biases (regret aversion and information cascade) and decision-making. The effects of other behavioral biases in real estate and stock market contexts should be examined in future research.